INTERNALISASI KARAKTER QURANI DENGAN TARTIL AL-QUR’AN - Qowim, Agus Nur (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
Tajweed knowledge must be mastered by every individual Muslim in order to achieve maximum results related to the worship of reading the Holy Qur'an. Reading the Qur'an when referring to Allah's commands must be done with maximum tartil, namely knowing and obeying every sign. The reward promised by God based on the words of the Messenger of Allah is that whoever reads one letter to him will be rewarded with one goodness which will also be multiplied 10 times. The miracle of the Qur'an does not stop there. When pondered more deeply, the knowledge of Tajweed contains a deep philosophy, not only getting rewards from God, but a deep understanding of its philosophy will produce a thought about internalization, namely guidelines for character formation, or morals in accordance with the guidance of the Qur'an.